Diferensiasi Strategi dalam Persaingan Bisnis Islam: Implikasi untuk Pemasaran Syariah Berbasis Nilai - Syalsabilah, Nabila (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2026)
In the era of globalization and increasingly fierce market competition, businesses are required to develop strategies capable of creating sustainable competitive advantages. In the context of Islamic economics, strategic differentiation is not only oriented towards product uniqueness and market advantage, but must also be based on Islamic values that uphold justice, honesty, and social responsibility. This study aims to analyze the application of strategic differentiation in Islamic business competition. Islamic marketing emphasizes the integration of economic and moral aspects through the principles of shiddiq, amanah, tabligh, and fathanah. Strategic differentiation in Islamic business is realized through the development of halal products, fair pricing, a transparent distribution system, and educational and ethical promotions. Thus, the implementation of strategic differentiation based on Islamic values is a crucial instrument in building competitiveness that is not only economically profitable but also provides blessings and sustainability in Islamic business. Keywords: Strategic Differentiation, Islamic Business Competition, Islamic Marketing, Islamic Values, Islamic Economics.